Transgenic Expression of Walleye Dermal Sarcoma Virus rv-cyclin Gene in Zebrafish and Its Suppressive Effect on Liver Tumor Development After Carcinogen Treatment - Zhan, H. (2014)
10.1007/s10126-009-9251-9